High thermoelectric performance of tellurium doped paracostibite. Issue 15 (22nd February 2016) - Chmielowski, R.; Bhattacharya, S.; Xie, W.; Péré, D.; Jacob, S.; Stern, R.; Moriya, K.; Weidenkaff, A.; Madsen, G. K. H.; Dennler, G.
Abstract : Paracostibite (CoSbS) has recently been identified as a promising thermoelectric material, yet its full potential remains to be attained. By carrying out an optimization of the experimental parameters, we achieve a power factor as high as 2.7 mW m −1 K −2 at 543 K. Abstract : Paracostibite (CoSbS) has recently been identified as a promising thermoelectric (TE) material, yet its full potential remains to be attained. We present herein an integrated method based on high throughput DFT computations validated with experiments that has allowed us to identify tellurium on antimony sites as a much more effective dopant than the formerly used nickel on cobalt sites. By carrying out a systematic adjustment optimization of the experimental parameters, we achieve a power factor as high as 2.7 mW m −1 K −2 at 543 K, which is maintained up to 730 K. This is, to the best of our knowledge, the largest value reported for polycrystalline metal sulfides.